EVALUATION OF ANTIHYPERLIPIDEMIC ACTIVITY OF METHANOLIC EXTARCT OF GLYCOSMIS PENTAPHYLLA ON EXPERIMENTALLY INDUCED HYPERLIPIDEMIA IN ALBINO RATS - GANTA RADHIKA REDDY; G. VENKATAIAH; MARRY REJEENA; D. SUDHARSHAN REDDY (International Journal of Pharma and Bio Sciences, 2014)
The present study was carried out on 60 male albino rats, divided into 10 groups 6 in each. Rats were post treated with normal saline, 200, 400mg/kg of MEGP and 10mg/kg of Atorvastatin as standard orally for triton and high cholesterol died induced hyperlipidemia models respectively. After administration of Triton and high diet cholesterol there is significant increase in the levels of TG and TC. The blood is withdrawn retro orbital method to estimate above serum parameters. Triton and high cholesterol treated group showed significance increase (P<0.0001) the levels of TC, TG, LDL & VLDL compared to normal group. Post-treatment with extract of Glycosmis pentaphylla at different doses (200mg/kg and 400mg/kg), significantly (P<0.001) prevented the elevation of these parameters when compared to hyperlipidemia rats. Triton and high cholesterol treated group showed significance (0.0001) decrease in HDL and compared to normal groups. Post-treatment with extract of Glycosmis pentaphylla at different doses (200mg/kg, 400mg/kg), significantly (P<0.001) prevented the reduction of these parameters when compared to hyperlipidemic rats. The present study suggests that post-treatment with methanolic extract of Glycosmis pentaphylla showed dose dependent antihyperlipidemic action against Triton and Cholesterol diet induced hyperlipidemia. The overall antihyperlipidemic action of methanolic extract of Glycosmis pentaphylla is probably due to its antioxidant, and free radical scavenging activity.